THE EFFECT OF SALTWATER FISH NANOPARTICLE POWDER CONSUMPTION ON TOOTH ENAMEL DENSITY In Vivo Study of Mice (Mus musculus) - Sandy Christiono; Fera Putri Ardiani; Welly Anggarani; Fourier Dzar Eljabbar (FKG Unlam, 2021)
ABSTRACTBackground: Dental caries is rarely found in children who eat saltwater fish. Overfished fish can be used as powder of saltwater fish nanoparticles, which is useful as an alternative material for the prevention of dental caries in dentistry can be used as a powder for saltwater fish nanoparticles, which is useful as an alternative material for preventing dental caries in dentistry. A Cone Beam Computed Tomography (CBCT), commonly known as a μ-CT Scanner, is a device used to quantify the increase in tooth enamel density Purpose: This study aimed to determine the effectiveness of saltwater fish nanoparticle powder consumption on tooth enamel density of Mus musculus. Method This study used an experimental research method with a randomized posttest only control group design. The research subjects were 16 mice taken from 2 pregnant female mice which were divided into two groups, namely the treatment group with 2.17 mg / 0.5 mL of saltwater fish nanoparticle powder and the control group which was given distilled water. Administration was carried out during the intrauterine period until the teeth of the mice grew, then observed the tooth enamel density with CBCT OP 3D Pro (KaVo, Germany). The data obtained were analyzed by Levene and continued with the Independent T-test. Result: The average value of enamel density in mandibular incisors in the treatment group was greater than the control group (p <0.05). Conclusion: Saltwater fish nanoparticle powder can increase tooth enamel density of Mus musculus. Keywords: CBCT, CT nanoparticle powder, saltwater fish, tooth enamel density,